The Mental Health Level of Flood Victims and Relationship with Disaster Impact in Sri Medan Batu Pahat Johor, Malaysia - Kirin, Arwansyah; Ismail, Faisal Husen; Sahimi, Mohd Shafiq; Mohammad, Che Adenan (2025)
Among the impacts caused by natural disasters is the increase in the mental health level of the people affected by the disaster. If it is allowed to drag on, it may interfere with their survival process. For example, the flood disaster that occurred in Sri Medan subdistrict, Batu Pahat Johor 2023, is suspected to have increased the mental health of the people affected by the disaster so efforts are needed to deal with it. This study aims to find out the mental health level of flood victims after the disaster and the correlation (relationship) between the mental health level of victims and the flood disaster that occurred in Sri Medan subdistrict, Batu Pahat. The population of respondents in this study is the community that became flood victims in the Sri Medan subdistrict, Batu Pahat. The sample taken was 207 respondents using a non-probability sampling technique, namely accidental sampling. Data collection was done through a survey using a questionnaire of 207 respondents who were spread out in the area of the Sri Medan subdistrict. Data analysis was done using a chi-square test and descriptive analysis. The results of the study show that the majority of the community's mental health level after the flood disaster is high with an overall mean of 3.67 and there is a significant correlation (p<0.05; r = 0.583) between the mental health level and the impact of floods to the community that became flood victims in Sri Medan subdistrict.